Do patent assets have a second life when startups fail? An analysis of the redeployment likelihood and mode of transfer - Serrano, Carlos J.; Ziedonis, Rosemarie H. (Strategic Management Journal, 2025)
Abstract Research Summary Entrepreneurial firms are fertile sources of patented inventions. Yet little is known about what happens to patent assets when startups go out of business: Do the assets have a “second life” through redeployment to new owners? Based on 264 failed VC‐backed startups, we document an active market for the patents both as standalone assets and through co‐movement with inventors to the purchasing organization. We then model and test how the redeployment likelihood and mode of transfer is shaped by trading thickness in the secondary patent market and the degree to which asset value is firm‐specific and tied to the original venture. The study sheds new light on conditions that affect the redeployment of intangible assets and the abilities of startups to preserve value in liquidation. Managerial Summary The process of innovation naturally gives rise to failed attempts and abandoned projects. While prior studies document that disbanded ventures are important sources of human capital and learning spillovers, we are the first to document an active resale market for their patent assets. This study shines new light on conditions that affect the redeployment likelihood and mode of patent transfer, whether as standalone assets or through co‐mobility with an inventor to the purchasing organization. The evidence is based on 264 VC‐backed startups in the semiconductor, software, and medical device sectors. The formal model and empirical findings suggest that trading conditions in the secondary market not only affect the likelihood that patents originating from failed startups will be sold but also influence managerial incentives to retain inventors and preserve complementarities with the human capital.